Monsters, Miracles and Missionary Journeys: Exploring a Historiographical Conundrum - Statham, Todd (International bulletin of mission research, 2026)
Miracles and wonders that testify to the power of the Christian God and his agents feature prominently in ancient and medieval missionary narratives and hagiography. A particularly dramatic example from the sixth century describes Columba vanquishing a river monster in Christ’s name to the wonderment of the heathen Picts. The conventions of modern historiography require that we demythologize a story like this. Yet a contemporary missionary narrative from Africa describes a similar encounter between an evangelist and a monster. By reading the two accounts analogously, this article challenges scholars of mission to move beyond limiting western intellectual postulates.